2009
DOI: 10.2109/jcersj2.117.732
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar resistance switching property of Al-Ag/La0.7Ca0.3MnO3/Pt sandwiches

Abstract: Bipolar resistance switching was investigated on La0.7Ca0.3MnO3 (LCMO) thin film with Al-Ag alloy top electrode (TE) including different Ag contents. The switching capability of Al-Ag/LCMO/Pt was greatly improved in Al-33%Ag TE structure compared to in Al-50%Ag TE structure. Switching times of faster than 100 ns and rewrite cycles of more than 400 were obtained while maintaining a ratio of resistance change larger than 1000%. The mechanism of resistance switching was explained by a model with interfacial nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Lanthanum Strontium Manganite : Oxides with perovskite structures have been reported as dielectrics of threshold switches and CBRAMs . Liu et al observed unidirectional threshold switching in a Pt/ a ‐La 0.3 Mn 0.7 SrO 3 /Ag system, where both electrodes and dielectric film were fabricated by sputtering (see Figure b).…”
Section: Methodsmentioning
confidence: 99%
“…Lanthanum Strontium Manganite : Oxides with perovskite structures have been reported as dielectrics of threshold switches and CBRAMs . Liu et al observed unidirectional threshold switching in a Pt/ a ‐La 0.3 Mn 0.7 SrO 3 /Ag system, where both electrodes and dielectric film were fabricated by sputtering (see Figure b).…”
Section: Methodsmentioning
confidence: 99%
“…The general structure of RRAM is shown in figure 8(a). Common electrode materials of RRAMs can be divided into five categories based on their composition or contribution to the resistive switching (RS) behavior, including elementary substance electrodes [59][60][61], alloy electrodes [62], silicon-based electrodes [63], nitridebased electrodes [64], and oxide-based electrodes [65]. On the other hand, storage media can be classified into organic storage media [66,67] and inorganic storage media [68].…”
Section: Embedded Rrammentioning
confidence: 99%